Cultural Capital Reclaimed for Future Investment - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
The Time to Write: Australian Women Writers 1890-1930 edited by Kay Ferres and That Shining Band: A Study of Australian Colonial Verse Tradition by Michael Ackland are reviewed by Elizabeth Perkins.